Study of Road Bitumen Operational Properties Modified with Phenol–Cresol–Formaldehyde Resin - Yuriy Demchuk; Volodymyr Gunka; Iurii Sidun; Bohdan Korchak; Myroslava Donchenko; Iryna Drapak; Ihor Poliuzhyn; Serhiy Pyshyev (Resources)
Using a relatively inexpensive method, phenol–cresol–formaldehyde resin (PhCR-F) was produced utilizing the byproducts of coal coking. It is shown that petroleum road bitumens, to which 1.0 wt.% PhCR-F is added, in terms of basic physical and mechanical parameters, comply with the requirements of the regulatory document for bitumens modified with adhesive additives. Research on the operational properties of these modified bitumens as a binding material for asphalt concrete is described. It has been proven that modified bitumen can store stable properties during its application (resistance to aging). The interaction of bitumens modified by PhCR-F with the surfaces of mineral materials, which occurs during the creation of asphalt concrete coatings, was studied. It was shown that adding 1.0 wt.% PhCR-F to road bitumen significantly improves the adhesion of the binder to the mineral material and increases the hydrophobicity of such a coating. The production of effective bitumen modifiers from non-target coking products of coal will not only make it possible to use new resources in road construction but will also increase the depth of decarbonization of the coking industry.